2016
DOI: 10.18632/oncotarget.7892
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell histiocytosis in adults: a case report and review of the literature

Abstract: BackgroundLangerhans cell histiocytosis (LCH) is a proliferative disease of histiocyte-like cells that generally affects children. Immunohistochemistry is essential to obtain the correct diagnosis, and treatment protocols are controversial.ObjectiveLangerhans cell histiocytosis (LCH) is easy to be misdiagnosed because of its various clinic features and laboratory results. This research focused on the clinicopathological, histopathological, immunohistochemical and other features of LCH and aimed to analyze LCH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 12 publications
0
83
0
1
Order By: Relevance
“…Although current experiences for the treatment of LCH suggest corticosteroids as a first choice of action, as was applied in this patient, there have been clinical studies that suggest corticosteroid therapy may be associated with a greater likelihood of deterioration than improvement [12]. The course of LCH is often difficult to predict, but in the present patient, her age, the fact that she suffered from the multi-system form of LCH, as well as having advanced cystic changes on HRCT and an active tuberculosis infection, definitely contributed to her lethal outcome [13,14].…”
Section: Discussionmentioning
confidence: 80%
“…Although current experiences for the treatment of LCH suggest corticosteroids as a first choice of action, as was applied in this patient, there have been clinical studies that suggest corticosteroid therapy may be associated with a greater likelihood of deterioration than improvement [12]. The course of LCH is often difficult to predict, but in the present patient, her age, the fact that she suffered from the multi-system form of LCH, as well as having advanced cystic changes on HRCT and an active tuberculosis infection, definitely contributed to her lethal outcome [13,14].…”
Section: Discussionmentioning
confidence: 80%
“…LCH is a rare and serious disease often diagnosed late because of its manifold symptoms 3, 10. The prognosis depends on the number of organs involved, the presence of organ dysfunction, and the patient's age.…”
Section: Discussionmentioning
confidence: 99%
“…Poor prognostic factors such as pulmonary LCH, liver function impairment, splenomegaly or bone marrow/ hematopoietic abnormity had been reported (1). Patients with MS-LCH with risk organ involvement also obtained higher mortality rate and shorten survival (1,3,4). Previous study had reported that more than 50% of investigated specimens contained a BRAF V600E gene mutation (4).…”
Section: Case Presentationmentioning
confidence: 91%
“…Physical examination revealed severe tenderness to touch over the sternum body and close to the manubrium. Blood hemogram revealed leukocytosis (white blood cell count: 13,140 cells/mm 3 ).…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation